Ophiopogon elatior, a new species of Asparagaceae from Yunnan, China - Lin, Qin-Wen; Le, Chi-Toan; Yu, Zhi-Yong; Sun, Guo-Feng; Liu, Bing (Phytotaxa, 2021)
Ophiopogon elatior from south-eastern Yunnan Province of China is described here as new to science. This species is morphologically similar to O. grandis, but differs from the latter species by leaf size (60–80 cm × 5–6 mm vs 25–55 cm × 7–11 mm), scape size (80–100 cm vs 15–20 cm), and flower color (purple-dotted vs white). Moreover, the new species can be easily distinguished from all known species of Ophiopogon with its erect and very tall scape highly overtopping the basal grass-like foliage.